The Role of Self-Efficacy Mediates the Influence of Attitudes, Subjective Norms, and Language Competency on the Behavior of Using Balinese Language Continuously - Ni Nyoman Kerti Yasa; Putu Laksmita Dewi Rahmayanti; I Gst Ngurah Jaya Agung Widagda; I Gusti Ayu Tirtayani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to examine and elucidate the mediating effect of self-efficacy on the influence of attitudes, subjective norms, language competency, and the desire to consistently utilize the Balinese language. The study's population comprises a younger generation of individuals from the Balinese community who have the responsibility of upholding the local culture through consistent utilization of the Balinese language. A purposive sampling strategy was employed, utilizing a sample size of 200 individuals. The used analytical methodology involves the utilization of Path Analysis through the implementation of Structural Equation Modeling with Partial Least Squares (SEM-PLS). The study findings indicate that attitude does not exert any influence on the continuous usage intention of Balinese. However, subjective norms demonstrate a positive and statistically significant impact on the continuous usage intention of Balinese. Additionally, Balinese language competence also exhibits a positive and statistically significant effect on the continuous usage intention of Balinese. Subsequently, the variables of attitude, subjective norm, and Balinese language competence exhibit a noteworthy and constructive impact on self-efficacy in Balinese language proficiency. Furthermore, self-efficacy demonstrates a positive and substantial influence on the intention to consistently utilize the Balinese language